Effect of adding fish emulsion and vermicompost on the growth of Tarragon (Artemisia dracunculus L.) - Abd , Najwan Abdulameer; Abdullah , Kadum Mohammed (Journal of Kerbala for Agricultural Sciences, 2024)
The experiment was carried out in the canopy of the Horticulture and Landscape Department - College of Agriculture - University of Kerbala during the spring semester of 2023. The study was implemented as a factorial experiment with a randomized complete block design (R.C.B.D.) with three replications. The experiment included two factors: fish emulsion (F), which was added at four concentrations: 0, 1, 2, 3% and added five times every two weeks, while the second factor was vermicompost (V), which was added before transferring the seedlings to the planting pots, at four levels: 0, 25, 50. 100 g pot-1. The results showed that adding fish emulsion had a significant effect on most vegetative growth traits, except for plant height and dry matter percentage, while adding Vermicompost had no significant effect on plant height and chlorophyll content of leaves, while it had a significant effect on the rest of the vegetative growth traits. The results of the intervention treatments between the study factors varied in their influence on the studied traits. The F4V4 intervention treatment gave the highest rate of plant height and number of branches, as it gave 85.16 cm and 32.50 branch plant-1, respectively, while the F2V3 treatment gave the highest rate of stem diameter of 3.127 mm, and F1V3 gave the highest rate of dry matter perce32wesaz2ntage, which gave 20.57%, and F3V3 the highest rate of leaf chlorophyll content, which gave 46.91 mg g-1 fresh weight. It can be concluded from this study that fertilizers resulting from organic waste can be used as fertilization sources for plants and combined with them to reduce the use of chemical fertilizers, reduce environmental damage, follow a sustainable agriculture system, and increase the efficiency of fertilizer use.